2018
DOI: 10.9758/cpn.2018.16.3.302
|View full text |Cite
|
Sign up to set email alerts
|

Depressive Temperament in Relatives of Patients with Schizophrenia Is Associated with Suicidality in Patients with Schizophrenia

Abstract: ObjectiveSuicide is a major cause of death in patients with schizophrenia; thus, predicting and preventing suicide in patients with schizophrenia is examined in various studies. Affective temperaments which are accepted as precursors of mood disorders may be an important factor in predicting suicidality. This study investigated the relationship between affective temperaments of relatives of schizophrenia patients and suicidal thoughts and other clinical correlates of patients with schizophrenia.MethodsPatients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
0
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 27 publications
1
0
0
Order By: Relevance
“…Results showed that higher total PANSS scores, negative PANSS and general PANSS were significantly associated with higher mean of depressive, irritable and cyclothymic temperament, in concordance with other studies [ 20 , 34 ]. The presence of positive and negative symptoms severely impacts the dynamics of social interactions making it difficult to establish a positive relationship which can often be frustrating to both the individual with schizophrenia and healthy subjects [ 35 ].…”
Section: Discussionsupporting
confidence: 91%
“…Results showed that higher total PANSS scores, negative PANSS and general PANSS were significantly associated with higher mean of depressive, irritable and cyclothymic temperament, in concordance with other studies [ 20 , 34 ]. The presence of positive and negative symptoms severely impacts the dynamics of social interactions making it difficult to establish a positive relationship which can often be frustrating to both the individual with schizophrenia and healthy subjects [ 35 ].…”
Section: Discussionsupporting
confidence: 91%
“…Şizofreni hastalarında ise yaşam boyu intihar riski %2 ila 5 arasında değişmektedir. Ancak hastalara intihar düşüncesi sorulduğunda %42 gibi yüksek oranlar görülmektedir (Yazici et al, 2018). Daha önce İspanyol gribi ve SARS virüsü salgını döneminde intihar ile ölümde artış bildirilmiştir (Wasserman, 1992;Yip, Cheung, Chau, & Law, 2010).…”
Section: Covid-19 Ve öZkıyımunclassified
“…Şizofreni hastalarında ise yaşam boyu intihar riski %2 ila 5 arasında değişmektedir. Ancak hastalara intihar düşüncesi sorulduğunda %42 gibi yüksek oranlar görülmektedir (Yazici et al, 2018). Daha önce İspanyol gribi ve SARS virüsü salgını döneminde intihar ile ölümde artış bildirilmiştir (Wasserman, 1992;Yip, Cheung, Chau, & Law, 2010).…”
Section: Covid-19 Ve öZkıyımunclassified